1996
DOI: 10.1080/10826079608014032
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Triacylglycerols inPanax Pseudo-Ginsengby HPLC Polymeric Column

Abstract: An improved high performance liquid chromatographic method was developed to determinate the active triacylglycerol principles of Panax pseudo-ginseng Wall. var. notoginseng Hoo & Tseng extracts. Chromatographic analysis is achieved on an isocratic system consisting of a polymeric reverse phase C , , column with a mobile phase of acetonitrile-methanol (5050, v/v) to elute the trilinolein and triolein. The eluted triacylglycerol are detected at 205 nm. The linear calibration range was 0.5-20 and 20-500 pgimL for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is reported that ginsenosides Rb 1 , Rb 2 , Rc, Rd, Re, Rf, Rg 1 , Rg 2 , F 2 , gypenoside XVII, and notoginsenoside R 1 could be detected in the wavelength of 203 and 198 nm [ [41] , [42] , [43] , [44] ]. The detection wavelength is set at 205 nm for trilinoleins [ 45 ], 254 nm for polyacetylenes [ 37 ], 260 nm for nucleobases and nucleosides [ 46 ], and 280 nm for phenolic compounds [ 38 ]. However, oleanane ginsenosides (ginsenoside Ro) are poor chromophores with weak UV absorption and are disturbed by solvents (the cut-off wavelength of methanol is 205 nm) that have low sensitivity with UV detection.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that ginsenosides Rb 1 , Rb 2 , Rc, Rd, Re, Rf, Rg 1 , Rg 2 , F 2 , gypenoside XVII, and notoginsenoside R 1 could be detected in the wavelength of 203 and 198 nm [ [41] , [42] , [43] , [44] ]. The detection wavelength is set at 205 nm for trilinoleins [ 45 ], 254 nm for polyacetylenes [ 37 ], 260 nm for nucleobases and nucleosides [ 46 ], and 280 nm for phenolic compounds [ 38 ]. However, oleanane ginsenosides (ginsenoside Ro) are poor chromophores with weak UV absorption and are disturbed by solvents (the cut-off wavelength of methanol is 205 nm) that have low sensitivity with UV detection.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these saponins were generally considered as chemical markers for the quality control of Radix et Rhizoma Notoginseng. Several methods have been developed for the analysis of the saponins, such as capillary supercritical fluid chromatography, [11] thin layer chromatography, [12][13][14] gas chromatography, [15,16] high performance liquid chromatography, [17][18][19][20][21] etc. Among them, HPLC coupled with different detectors was the most common used method for determination of the saponins.…”
Section: Introductionmentioning
confidence: 99%